ANALISIS PENGUKURAN KINERJA PADA PD. BPR BKK BANJARHARJO KABUPATEN BREBES DENGAN PENDEKATAN BALANCED SCORECARD - P., Medi Tri; Lukiastuti, Fitri; Rachmansyah, Yanuar (PRESTASI, 2012)
This research was conducted at the scope of PD BPR BKK Bandarharjo, Regency of Brebes. The aims of research were: (1) to analyze organizational performance by conventional concept through CAMEL criterion dan Balanced Score Cards concept through four perspectives. (2) to analyze the difference between performance appraisal results between conventional concept and Balanced Score Card concept.The focus of research was application of Balanced Score Card concept in management performance appraisal. Population of research was financial report data from merger process since 2007 until 2010 and population of depositors was 2.946 persons at 2010 and population of employees was 42 persons. Sample of financial report was assorted from 2008 until 2010. Whereas, the number of samples of employees were 100 persons.Both primary and secondary data were used in this research. Primary data was obtained through interview to get information from the respondent and questionnaires to measure customers satisfaction level. Later, to the questionnaires, validity and reliability test were conducted. Through both test, validity and reliability criterions could be fulfilled.To measure institutional performance, conventional appraisal through CAMEL criterion and appraisal based on Balanced Score Card method were applied. CAMEL criterion including Capital, Assets Quality, Management, Earning, and Liquidity. Whereas, performance appraisal based on Balanced Score Card method including financial, customers, internal process, and growth and learning perspectives.Based on both performance appraisal methods, several conclusions formulated were:Â (1) Institutional performance appraisal through conventional concept that was focused on only financial aspects just could give historical results and it could not measure non financial performance. (2) Institutional performance appraisal throughÂ four Balanced Score Cards perspectives criterions (financial, customers, internal process, and growth and learning perspectives) showed that generally, this financial institution had been able to run the business well. (3) There was difference between performance appraisal through conventional concept and Balanced Score Cards criterions. It indicated that conventional method could measure corporate success level from financial point of view only. Whereas, Balanced Score Cards concept could give more comprehensive information because it could give performance appraisal from both dinancial and non financial aspects and being able to create new strategy in the future.Keywords: CAMEL, Balanced Score Cards, dan institutional performance